Penerapan Linear Sequential Model Dalam Merancang Aplikasi Penjualan Pakaian Berbasis Web Pada Distro Kael - Eriek Orlando; Melani Dewi Lusita; S Sudjiran (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This research aims to apply a sequential linear model in the development of a web-based clothing sales application, with a case study at Distro Kael. This development method involves sequential steps in system design, starting from inventory management, ordering, to payment. The main emphasis is placed on ease of use, responsiveness of the interface and a satisfying shopping experience. The implementation of the linear sequential model is expected to increase distro operational efficiency and provide a more structured shopping experience for customers. The evaluation results will include application performance, system responsiveness, and user satisfaction level, as indicators of the success of implementing this model in the context of online clothing sales at Distro Kael.